Brain Protection pada Traumatik Brain Injury - Sudadi (Jurnal Komplikasi Anestesi, 2023)
Trauma is the leading cause of death in children and people under 45 years old, and brain trauma is the leading cause of death in 25% of cases. Brain trauma can be classified as both primary and secondary injury. Primary brain injury is a direct result on the head causing both anatomical and physiological damage. Secondary brain injury is the result of hypotension, hypoxia, acidosis, edema, or other advanced factors that cause damage to brain tissue. Brain protection as prevention and improvement of neuronal damage caused by abnormalities of cerebral metabolism, histopathological or neurological functioning that occurs after hypoxia or ischemic conditions. The key elements in brain protection that must be achieved are lowering oxygen demand, increasing oxygen supply and halting intracellular pathological processes.